Coronavirus disease 2019 (Covid-19) outbreak lockdown: the effects on spiritual, physical, emotional, intellectual and financial states of the Islam believers - Mohd Arof, Khairul Zahreen; Awang, Mohd Daud; Abd Rashid, Mohd Hambali; Ismail, Syuhaida (University of Management and Technology, 2021)
Coronavirus Disease 2019 (COVID-19) outbreak was declared by the World Health Organization (WHO) as a global health emergency and global pandemic on March 11, 2020. In controlling the quick spreading of COVID-19, the enforcement of lockdown has been employed in many counties. Unfortunately, the lockdown affects all industries as well as the whole nation in terms of spiritual, physical, emotional, financial, and intellectual states. Therefore, this paper attempts to examine the effects of lockdown on spiritual, physical, emotional, intellectual, and financial states of the Islam believers from Malaysia, Oman, Yemen, Saudi Arabia, Egypt, and Turkey. Through systematic literature review, this paper designed a questionnaire survey and collected information from 208 respondents. Prior to the primary data collection, a pilot study was conducted to test the reliability of the designed questionnaire survey. This paper found that the COVID-19 lockdown has positive effects on the spiritual, intellectual, and physical states of the believers of Islam. On the other hand, the COVID-19 lockdown also leads to unstable emotion of the believers of Islam as well as the financial issues. The findings may help in future study, religious departments, and the authority bodies of the countries to strategize the plan of actions in minimising the impact of lockdown on the nations.